METHODS OF FORMING AESTHETIC EDUCATION THROUGH TEACHING PRODUCTION TECHNOLOGY DEPARTMENT TO STUDENTS OUTSIDE THE CLASSROOM AND SCHOOL - Egamova , Anbarjon Atanazarovna; Ismailova, Momogul Hamraboyevna (Educational Research in Universal Sciences, 2024)
This article describes the importance and methods of teaching the department of product production technology in forming the aesthetic education of students in general education schools and the topic of using innovative pedagogical technologies in teaching.